Rapid clinical pharmacology : a student formulary - Batchelder, Andrew; Rodrigues, Charlene ;Alrifai, Ziad (Hoboken, New Jersey : John Wiley & Son, Inc., 2011)
This pocket reference guide is a must for all medical students and junior doctors preparing for exams in pharmacology or needing a rapid reminder during a clinical attachment. In light of the growing pressures on those who prescribe drugs to patients, increasing emphasis has been placed on the importance of pharmacology in the undergraduate medical curriculum. Rapid Clinical Pharmacology, with its concise, easy-to-use approach, offers an appealing format for students to use in both clinical practice and exam preparation and its 'one-page per drug/class' layout easily facilitates the generation.
Gastrointestinal system -- Cardiovascular system -- Respiratory system -- Central nervous system -- Infections -- Endocrine system -- Obstetrics, gynaecology and urinary tract disorders -- Malignant disease and immunosuppression -- Musculoskeletal and joint disease -- Eye -- Anaesthesia -- Intravenous fluids -- Blood and transfusion medicine